The relevance of clinical and radiographic features of jaw lesions: A prospective study - Juliane Piragine ARAUJO; Celso Augusto LEMOS; Thais Gimenez MINIELLO; Fabio Abreu ALVES
Abstract The study was carried out in a Brazilian population and the aim was to describe the prevalence and the clinic-radiographical features of jaw lesions. In addition, a comparison between the main diagnosis hypothesis and final diagnosis was accessed. A prospective study which evaluated all patients with jaw lesions diagnosed in an Oral Diagnosis Center, between August 2013 and October 2014. A total of 450 patients were observed for the first time, and 130 had some type of jaw lesion. The mean age of the patients was 35.2 years ± 17.86. Among these, 71 were women (54.62%) and 87 were Caucasian (66.92%). The mandible was affected more frequently (71.43%) than the maxilla (28.57%). Swelling and pain were the most frequent clinical signs and symptoms and were observed in 60 (42.85%) and 38 (27.14%) cases, respectively. The panoramic x-ray was the main radiographic exam utilized (88.57%). Radiolucent lesions accounted for 89 cases (63.57%) and the unilocular form was present in 114 cases (81.43%). A total of 93 cases had histopathological analyses and the periapical cyst was the most frequent lesion. In the other 47 lesions, the diagnosis was conducted by clinical and radiographic management. Bone lesions were frequent, being noted on first visit in approximately 30% of patients; in 1/3 of the cases, the diagnoses were completed with a combination of clinical and radiographic exams.